Planar AFM macro-probes to study the biomechanical properties of large cells and 3D cell spheroids. (August 2019) - Andolfi, Laura; Greco, Silvio L.M.; Tierno, Domenico; Chignola, Roberto; Martinelli, Monica; Giolo, Elena; Luppi, Stefania; Delfino, Ines; Zanetti, Michele; Battistella, Alice; Baldini, Giovanna; Ricci, Giuseppe; et al.
Graphical abstract: Abstract: The ability to measure mechanical response of cells under applied load is essential for developing more accurate models of cell mechanics and mechanotransduction. Living cells have been mechanically investigated by several approaches. Among them, atomic force microscopy (AFM) is widely used thanks to its high versatility and sensitivity. In the case of large cells or 3D multicellular aggregates, standard AFM probes may not be appropriate to investigate the mechanical properties of the whole biological system. Owing to their size, standard AFM probes can compress only a single somatic cell or part of it. To fill this gap, we have designed and fabricated planar AFM macro-probes compatible with commercial AFM instruments. The probes are constituted of a large flat compression plate, connected to the chip by two flexible arms, whose mechanical characteristics are tuned for specific biological applications. As proof of concept, we have used the macro-probes to measure the viscoelasticity of large spherical biological systems, which have a diameter above 100 μm: human oocytes and 3D cell spheroids. Compression experiments are combined with visual inspection, using a side-view configuration imaging, which allows us to monitor the sample morphology during the compression and to correlate it with the viscoelastic parameters. Our measurements provide a quantitative estimate of the relaxation times of such biological systems, which are discussed in relation to data present in literature. The broad applicability of the AFM macro-probes can be relevant to study the biomechanical features in any biological process involving large soft materials. Statement of Significance: The understanding of the role of physical factors in defining cell and tissue functions requires to develop new methods or improve the existing ones to accurately measure the biomechanical properties. AFM is a sensitive and versatile tool to measure the mechanical features from single proteins to single cells. When cells or cell aggregates exceed few tens of microns, AFM suffers from limitations. On these biological systems the control of the contact area and the application of a precise uniform compression becomes crucial. A modification of the standard cantilevers fabrication allowed us obtaining AFM macro-probes, having large planar contact area and spring constant suitable for biological investigations. They were demonstrated valuable to characterize the mechanical properties of large hierarchical biological systems.